Downhill turn techniques and performance in cross-country skiing: Associations with mechanical and physical parameters - Bucher, S.; Supej, M.; Sandbakk, O.; Holmberg, H. C. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
INTRODUCTION: Downhill turns in cross-country skiing are performed in widely varying conditions. In order to effectively utilize potential energy and accelerating forces, skiers adapt the entrance velocity, the trajectories throughout the turn and the employment of different techniques. The aim of this study was to characterize the main techniques utilized in downhill turns among elite cross-country skiers and to examine how downhill turn performance is influenced by technique distribution, mechanical parameters and the skiers` maximal power characteristics. METHODS: 12 female elite cross-country skiers performed six highly standardized subsequent turns using a freely chosen technique. The subjects were continuously monitored by a high-end real time kinematics GNSS and one camcorder. The measured trajectory was used for calculating total and intersection time, velocity and energy dissipation at each point of observation, and was linked to the use of technique. Additionally, maximal isometric squats and counter-movement jumps were performed to characterize the athletes` maximal strength and power. RESULTS: Three techniques with significantly different mechanical patterns were employed by the skiers: side stepping, skidding and ploughing. The typical technique distribution for the best skiers was a short phase of skidding at the beginning of the turn, followed by an early transition to and overall greater proportion of side stepping. An early transition between the decelerating and accelerating phase and high velocity at the transition point were strongly correlated to the performance variables (i.e., time and energy dissipation; all p<0.05). Furthermore, better skiers` turns are related both to higher velocities and shorter trajectories (all p<0.01). Peak force, time to peak force and rate of force development in absolute values were most strongly correlated with performance (all p<0.05). CONCLUSIONS: This study identified technique distribution and mechanical parameters linked to better downhill turn performance in cross-country skiing. Better skiers preferred skidding to ploughing and showed an earlier initiation and overall greater use of the side stepping technique. The athletes` absolute maximal power is linked to the ability to ski at a high velocity and with short trajectories throughout.